Exploring the critical dependence of the adsorption of various dyes on the degradation rate using a ferrihydrite surface under visible light. Issue 37 (24th March 2016) - Liu, Shan; Ni, Chunyan; Su, Hui; Liu, Hui; Chen, Rufen; Li, Ping; Wei, Yu
Abstract : The strength of the affinity between dyes and ferrihydrite has an important influence on their degradation rate in a Fenton-like system. Abstract : The adsorption and degradation of Mordant Yellow 10 (MY10), Eriochrome Black T (EBT) and Phenol Red (PR) in a ferrihydrite (Fh)/H2 O2 /visible light system were investigated. The affinity of Fh to the three dyes was evaluated based on the Langmuir model parameters, dimensionless separation factor R L, and adsorption–desorption isotherms. The effects of the affinity between the dyes and Fh on the degradation rate of the dyes were studied. The results show that the saturated adsorption capacities of the three dyes on Fh were 206.61, 126.26, and 73.26 mg g −1 for EBT, MY10, and PR, respectively. The degradation rate of EBT was much larger than those of MY10 and PR, but the difference between the degradation rates of MY10 and PR were small. The affinity between the dyes and Fh followed the order of MY10 ≫ EBT > PR. Both strong and weak affinities between the dyes and Fh were unfavorable for their degradation. Only moderate affinity allowed the adsorption–degradation–desorption process of dyes to occur continuously, which resulted in a high degradation rate. When NaNO3 solution was added into the MY10 system, the affinity between MY10 and Fh weakened, and the degradation rate of MY10 increased.